Discovery of Mycobacterium avium subsp. paratuberculosis Lytic Phages with Extensive Host Range Across Rapid- and Slow-Growing Pathogenic Mycobacterial Species - Aleen Clare Golla; Jeanne Chaumontet; Rebecca Vande Voorde; Lia Danelishvili (Antibiotics)
Background/Objectives: Developing interventions for Johne’s disease, which focuses on controlling Mycobacterium avium subsp. paratuberculosis (MAP) in contaminated environments by treating infected cows and preventing transmission from diseased animals, is a critical priority. Bacteriophage (phage) therapy, an emerging biological intervention, offers a promising alternative for the treatment and management of MAP infections. Methods: In this study, we generated an MAP-specific lytic phage library aimed at characterizing the therapeutic potential of phages under environmental and biological conditions that mimic those encountered in infected cattle such as ruminal fluid, milk, colostrum, and the bovine intestinal epithelium, a key site of MAP colonization and, later, transmission. Results: Our library contains a diverse collection of phages that have demonstrated robust lytic activity against MAP. The host range of these phages was thoroughly assessed, revealing that several isolates produce clear plaques on a range of MAP strains, as well as other pathogenic non-tuberculous mycobacterial (NTM) species and M. tuberculosis strains. This broad host range expands the therapeutic potential of the phage collection, positioning it as a potential cross-species antimicrobial tool. In vitro tests under conditions replicating the rumen, milk, and colostrum environments show that selected phages maintain stability and lytic efficacy, even in the presence of complex biological fluids. Furthermore, a subset of these phages was capable of preventing MAP colonization and invasion in cultured bovine epithelial cells, suggesting their potential for direct prophylactic application in cattle. Conclusions. Our collection of MAP phages represents a valuable source that can be developed into probiotic-like preparations, offering a cost-effective solution for prophylaxis and control of Johne’s disease.